Carbohydrate fermentation by gut microflora in preterm neonates. Issue 10 (October 1989) - Walker, V; Mills, G A; Hall, M A; Lowes, J A
Abstract : To study organic acid excretion, urine was collected from 52 preterm infants at weekly intervals and analysed by capillary gas chromatography-mass spectrometry. Twelve of 22 babies born before 33 weeks' gestation excreted 2, 3-butanediol, as did six born between 33 and 36 weeks. Six very immature babies also excreted acetoin, the metabolic precursor of the diol. Other products derived from carbohydrate included methylmalonic and ethylmalonic acids in one baby, and D-lactic acid in five. Acetoin has never been found in urine before, and the other four acids have been found only rarely. Excretion of these metabolites by preterm babies can be explained by increased intestinal permeability, unabsorbed lactose in the colon, and colonisation with certain opportunistic micro-organisms prevalent in neonatal units, including klebsiella, serratia, and enterobacter. The findings support evidence from breath hydrogen analysis that carbohydrate fermentation takes place in the gut of preterm infants.